Reductant free green synthesis of magnetically recyclable MnFe2O4@SiO2-Ag core- shell nanocatalyst for the direct reduction of organic dye pollutants - Erturk, Ali Serol; Elmaci, Gokhan; Gurbuz, Mustafa Ulvi (Tubitak Scientific & Technological Research Council Turkey, 2021)
The present paper describes in situ green immobilization of silver nanoparticles on MnFe2O4@SiO2 nanospheres using Epilobium parviflorum (EP) without using any other toxic chemicals and reducing or stabilizing agents. The morphology, composition, and magnetic properties of the resulting MnFe2O4@SiO2-Ag core-shell nanocatalyst were characterized by scanning electron sample magnetometer (VSM), and attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR). The catalytic performance of the synthesized MnFe2O4@SiO2-Ag was employed on the organic pollutants dyes such as rhodamine B (RhB) and methylene blue (MB). The results revealed significant reduction performances for the MB (116.28 s-1 g-1) and RhB (27.12 s-1 g-1) over the existing literature. Furthermore, the MnFe2O4@SiO2-Ag exhibited high stability for the completion of the reduction of RhB between the reaction times of 13.1 (first) and 19.8 min (final) with the 100% decolorization efficiency even after several cycles with an excellent magnetic separation. Overall, this work demonstrates a simple and practical green synthetic route for the preparation of magnetic recyclable core-shell nanocatalyst that can be a good candidate for the treatment of organic contaminants in wastewater adhering to green chemistry principles for the environmental pollution concerns.
Keywords: Magnetic recyclable nanocatalyst; Epilobium parviflorum; silver nanoparticle; heterogeneous catalyst; reduction of organic dyes; ONE-POT SYNTHESIS; CATALYTIC-REDUCTION; AZO DYES; FERRITE NANOPARTICLES; FE3O4 NANOPARTICLES; SILICA MICROSPHERES; ENHANCED REMOVAL; NITRO-COMPOUNDS; GRAPHENE OXIDE; EFFICIENT; Chemistry; Engineering